KETIMPANGAN KUASA DALAM FILM DOKUMENTER MILITER AMERIKA DI AFGANISTAN RESTREPO - Pujarama, Widya (LAYAR: Jurnal Ilmiah Seni Media Rekam, 2017)
Media provides the society with limited perspective of realites, making the world phenomenon never be exact same with the media depiction. In most of the situated war, depicted on media, the war has become more about descriptions rather than a causal explanation, as a result, the war phenomenon is simplified. The simplification highlights the humanization of individuals depicted from the filmmaker’s culture, and distanced individuals from other cultures. The one sided portrayal tend to mix military world with emotional side of soldiers’ life called militainment coined by Stahl (2010). One of the American film titled Restrepo (2009) accentuates the life of American soldiers’ in one of the most dangerous outposts during the war against the Taliban in Afghanistan. The war documentary film has become a product of information and entertainment-blurred genre as a result of embedding journalism. This essay will use textual analysis methodologies of McKee’s (2003:92), in particular, to highlight (1) representation of US domestic patriotism in relation to Bush administration’s invasion ideology of Afghanistan war in 2001-present; and (2) the racist depictions of Afghani locals in Restrepo documentary. It is concluded that positive portrayal of soldiers’ life in the war zone and asymmetric relationship of American soldiers and the Afghans intensified the US status quo as superpower country towards the Afghans as the Orient.